Topological defects of dipolar bose-einstein condensates with dresselhaus spin-orbit coupling in an anharmonic trap - Yang, Hui; Gao, Yan; Yu, Bo; Zhang, Jinhua (Frontiers in Physics, 2022)
We consider the topological defects and spin structures of binary Bose-Einstein condensates (BECs) with Dresselhaus spin-orbit coupling (D-SOC) and dipole-dipole interaction (DDI) in an anharmonic trap. The combined effects of D-SOC, DDI and anharmonic trap on the ground-state phases of the system are analyzed. Our results show various structural phase transitions can be achieved by adjusting the magnitudes of the D-SOC and DDI. Meantime, a ground-state phase diagram is given as a function of the D-SOC and DDI strengths. In addition, we find that tuning the D-SOC and the DDI can derive novel rich topological configurations, including ghost vortex, half-quantum vortex, skyrmion pair, vertical skyrmion string and horizontal skyrmion string.